Development, Characterization and Experimental Validation of a Cultivated Sunflower (Helianthus annuus L.) Gene Expression Oligonucleotide Microarray - Fernández, Paula (2012)
Fil: Soria, Marcelo Abel. Universidad de Buenos Aires. Facultad de Agronomía. Buenos Aires, Argentina.